Analysis of multidimensional factors in attempts to quit using tobacco by Korean adolescents - Mi-Jung Kang; Hyunjin Lee; Mirae Jo (Komiyama Printing Co. Ltd, 2020)
Abstract Background This study aims to understand the extent of adolescents' attempts to quit using tobacco and the factors influencing such attempts in Korea, using a descriptive, cross-sectional design and secondary data analysis with the 2019 Youth Health Behavior Survey. Methods The participants were 4028 adolescent tobacco users who had used tobacco for 1 day or more in the past 30 days. The data analysis was performed using IBM SPSS/WIN 26.0 program, and multivariable logistic regression analysis was conducted using the complex sampling method module. Results A total of 68.2% of the participants attempted to quit using tobacco. We analyzed the factors for adolescents' attempts to quit using tobacco by dividing them into psychological, physical, behavioral, and environmental dimensions. The factors influencing adolescents' attempts to quit using tobacco, identified through multivariable logistic regression analysis, are as follows: participation in sports activities (OR = 1.20, 95% CI 1.01-1.41), vigorous physical activity (OR = 1.24, 95% CI 1.06-1.46), and type of tobacco product used (OR = 1.65, 95% CI 1.24-2.21) in the behavioral dimension; pictorial cigarette pack warnings (perceived smoking as unhealthy) (OR = 1.91, 95% CI 1.56-2.36), and the presence of secondhand smoking at home (OR = 1.18, 95% CI 1.01-1.38) in the environmental dimension. Conclusions Schools and public healthcare providers must consider multidimensional factors when providing support for successful tobacco cessation in adolescents and focus particularly on elements relating to physical activity and environmental factors.